THE EFFECT OF COLLABORATION AND COOPERATION IN THE PROFESSIONAL DEVELOPMENT OF TEACHERS IN EARLY CHILDHOOD EDUCATION - Nuraisah, Mia; Marwiji, Muh. Hasan (Epistemic: Jurnal Ilmiah Pendidikan, 2024)
This study indicates that the quality of learning in Indonesia has not met expectations, impacting student achievement, which remains less satisfactory, especially compared to other countries. One contributing factor is the low level of teacher professionalism, particularly in early childhood education institutions. This study aims to analyze the effect of collaboration and cooperation in the professional development of early childhood teachers. The method used is descriptive qualitative, where data is collected without limited categories, allowing researchers to explore specific issues in depth relevant to the research objectives. This study is categorized as library research, where researchers analyze several relevant articles and collect data for further analysis. The results show that collaboration and cooperation significantly influence the development of teacher professionalism. Enhancing teacher professionalism must be carried out continuously in line with developments in science, technology, and society. This approach can be implemented through collaboration techniques, fostering a learning organizational culture, and training activities, both individually and in groups, to improve overall institutional performance.